2020
DOI: 10.1155/2020/3534570
|View full text |Cite
|
Sign up to set email alerts
|

The Antiaggregative and Antiamyloidogenic Properties of Nanoparticles: A Promising Tool for the Treatment and Diagnostics of Neurodegenerative Diseases

Abstract: Due to the progressive aging of the society, the prevalence and socioeconomic burden of neurodegenerative diseases are predicted to rise. The most common neurodegenerative disorders nowadays, such as Parkinson’s disease, Alzheimer’s disease, and amyotrophic lateral sclerosis, can be classified as proteinopathies. They can be either synucleinopathies, amyloidopathies, tauopathies, or TDP-43-related proteinopathies; thus, nanoparticles with a potential ability to inhibit pathological protein aggregation and/or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Amyloid aggregates are commonly associated with proteinopathies [42], and their association with cellular components underlies the gain of toxic function of such aggregates. The dysfunction of the ubiquitin–proteasome system, loss of transcriptional regulation, ER stress, impairment of axonal transport and mitochondrial dysfunction are certain examples of cellular malfunctions that are observed in neurodegenerative disorders [43].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid aggregates are commonly associated with proteinopathies [42], and their association with cellular components underlies the gain of toxic function of such aggregates. The dysfunction of the ubiquitin–proteasome system, loss of transcriptional regulation, ER stress, impairment of axonal transport and mitochondrial dysfunction are certain examples of cellular malfunctions that are observed in neurodegenerative disorders [43].…”
Section: Discussionmentioning
confidence: 99%
“…This brings up a question as to whether the accumulated proteins on the surface of nanoparticles could aggregate and become toxic. As for αS, the major causative protein in PD, ample evidence from studies in buffer system has shown that the promotive or inhibitive effects of nanoparticles on this protein are determined by multiple factors, such as shape, surface charge, and concentration ( D’Onofrio et al, 2020 ; Pichla et al, 2020 ). However, there were only limited studies focusing on the effect of nanoparticles on αS aggregation in cellular and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles are defined as particle matters with the size of 1–100 nm in at least one dimension of measurement [106] , [107] ( Review ). They have attracted many interests as one of the most promising therapeutic and diagnostic agents due to their small size [108] , ability to penetrate the blood-brain barrier [109] , rapid clearance [110] and high flexibility in terms of the ease of modification [106] .…”
Section: Introductionmentioning
confidence: 99%